Analysis of the Effectiveness of Collecting Regional Economic Data through the Business Tagging System: A Study at BPS Sidoarjo: Analisis Efektivitas Pengumpulan Data Ekonomi Regional melalui Sistem Tagging Usaha: Studi pada BPS Sidoarjo - Yunita Wulandari; Sofia Naya Febriyanti; Satrio Sudarso (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Reliable economic statistics form the foundation for policy-making and regional development planning. Specific Background Central Statistics Agency in Sidoarjo implements digital business tagging using SW Maps and Kendedes Mobile to record multi-scale business units. Knowledge Gap Previous research primarily examined paper-based or web-based surveys, leaving the effectiveness of geospatial business tagging unexplored. Aims This study analyzes the effectiveness of business tagging in supplying accurate data for regional economic planning. Results Findings demonstrate that digital tagging enhances spatial recording accuracy, streamlines Statistical Business Register profiling, and minimizes data duplication through clear field tracking mechanisms. Novelty The research establishes an empirical framework integrating mobile GIS applications into local business directory updates for economic censuses. Implications Digital tagging significantly improves regional gross domestic product estimation, supporting data-driven economic governance and sustainable policy formulation. Key Findings Highlights Mobile tagging applications significantly streamline field business profiling and geocoding precision. Integrated digital directories prevent redundant data collection in regional business registers. Enhanced business registry accuracy directly improves regional economic planning and census preparation. Keywords: Business Registration, Regional Economy, Statistical Business Register, Digital Technology, Geospatial Tagging